THE MYSTICAL LANDSCAPE OF TUJJAR SHARIEF: A STUDY OF ZIYARAT MAQDOOMI SAHIB - Shabir Ahmad Lone; Rifat Shabir (Journal of International Islamic Law, Human Right and Public Policy, 2026)
Ziyarat Maqdoomi Sahib, situated at Tujjar Sharief in the Sopore–Zaingeer region of north Kashmir, is one of the most respected Sufi shrines of the area. It is associated with Hazrat Sheikh Hamza Makhdoom (RA), popularly known as Maqdoomi Sahib, and reflects the strong Sufi traditions and shared cultural values of Kashmir. Since medieval times, the shrine has served not only as a place of prayer but also as a centre for spiritual learning, moral teachings, and social unity. Devotees from different parts of Kashmir visit the shrine regularly, regardless of their social or economic background. Daily prayers and annual religious gatherings highlight the living Sufi spirit of humility, devotion, and compassion. The calm natural surroundings and simple architecture add to its peaceful and spiritual environment. Culturally and socially, the shrine has helped preserve local traditions, oral stories, and devotional practices, while promoting communal harmony. Today, it also holds potential for pilgrimage and cultural tourism if developed carefully, ensuring that its spiritual character is protected. This paper examines the historical background and legacy of Ziyarat Maqdoomi sahib, a famous shrine in the Tujjar Sharief Zaingeer, Sopore Baramulla District of Kashmir Valley.